PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA MIO M3 125 PADA PT HARPINDO JAYA CABANG NGALIYAN SEMARANG - Ibnu Setiobudi, 12.05.51.0053; Wuryan, Sophiyanto (Students' Journal of Economic and Management, 2016)
Consumer purchasing behavior is unique because of the preference of everyone to a different product. It is influenced by many factors, including price, product quality, service quality, differentiation and other promotions. The purpose of this study was to analyze the effect of product quality, perceived price and promotions on purchasing decisions Yamaha Mio motorcycle M3 125 PT Jaya branch Harpindo Ngaliyan Semarang, either partially or simultaneously. Data used in this study are primary data obtained directly from the original source. While the techniques used for data collection using a questionnaire to ask a number of written questions that are used to obtain information and respondents. The sample in this study is that consumers who buy and use the M3 125 Mio motorcycle on Harpindo Jaya Branch Ngaliyan Semarang as many as 100 people. The sampling technique used purposive sampling is a sampling technique on certain considerations that consumers who buy and use the M3 125 Mio motorcycle on Harpindo Jaya Branch Ngaliyan Semarang. Test equipment in this study using multiple linear regression. The results of the analysis can be concluded that: The product quality has positive influence on purchase decisions. The better the quality of the product, it will increase the purchasing decision. Perception price positive influence on purchase decisions. The better the perception of the price, then the buying decision will increase. Promotion of positive influence on purchase decisions. The more times the intensity of the sale, then the purchase decision will increase. Product quality, price perception and promotion of positive influence jointly on purchasing decisions. Keywords: product quality, price perception, promotion and purchasing decisions .